Segregation of phenotypic characteristics in hybrids of Triatoma brasiliensis species complex (Hemiptera, Reduviidae, Triatominae) - Pinotti, Heloisa [UNESP]; Alevi, Kaio Cesar Chaboli [UNESP]; de Oliveira, Jader [UNESP]; Ravazi, Amanda [UNESP]; Madeira, Fernanda Fernandez [UNESP]; dos Reis, Yago Visinho [UNESP]; de Oliveira, Ana Beatriz Bortolozo [UNESP]; de Azeredo-Oliveira, Maria Tercília Vilela [UNESP]; da Rosa, João Aristeu [UNESP] (Elsevier, 2021)
There are currently 156 species, grouped into 18 genera and five tribes included in the subfamily Triatominae. All of them are potential vectors of Chagas disease. Triatoma is paraphyletic and the species of this genus have been grouped into complexes and subcomplexes. Triatoma brasiliensis complex is a monophyletic group composed of eight taxa: T. b. brasiliensis, T. b. macromelanosoma, T. juazeirensis, T. sherlocki, T. petrocchiae, T. lenti, T. bahiensis, T. melanica. Experimental crosses have helped in systematic, taxonomic and evolutionary issues of these vectors. Based on this, we carried out experimental crosses between T. lenti and four other species of the T. brasiliensis complex and analyzed the segregation pattern of phenotypic characteristics of T. lenti, T. b. brasiliensis, T. b. macromelasoma, T. juazeirensis and T. melanica in the hybrids. The hybrids resulting from the crosses between T. b. brasiliensis ♀ x T. lenti ♂, T. juazeirensis ♀ x T. lenti ♂, and T. melanica ♀ x T. lenti ♂ showed segregation of characteristics of both parental species. On the other hand, the hybrids between T. lenti ♀ x T. juazeirensis ♂, T. b. macromelasoma ♀ x T. lenti ♂, and T. lenti ♀ x T. melanica ♂ showed a specific pattern of T. lenti, T. lenti and T. melanica, respectively. Thus, the pattern of segregation of morphological characteristics between species of the T. brasiliensis complex was characterized. These results highlight the importance of integrative taxonomy for the correct identification of Chagas disease vectors grouped in the T. brasiliensis complex if natural hybridization events occur.
Keywords: Chagas disease vector; Evolution; Morphology; Triatomines